2007
DOI: 10.7155/jgaa.00150
|View full text |Cite
|
Sign up to set email alerts
|

Large-Graph Layout Algorithms at Work: An Experimental Study

Abstract: In the last decade several algorithms that generate straight-line drawings of general large graphs have been invented. In this paper we investigate some of these methods that are based on force-directed or algebraic approaches in terms of running time and drawing quality on a big variety of artificial and real-world graphs. Our experiments indicate that there exist significant differences in drawing qualities and running times depending on the classes of tested graphs and algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 20 publications
0
50
0
1
Order By: Relevance
“…They are all at least an order of magnitude faster than Fruchterman and Reingold's grid-variant algorithm, and generally produce much better layouts [7].…”
Section: Force-based Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…They are all at least an order of magnitude faster than Fruchterman and Reingold's grid-variant algorithm, and generally produce much better layouts [7].…”
Section: Force-based Methodsmentioning
confidence: 99%
“…The classical MDS (CMDS) algorithm by Kruskal and Seery [14], one of our comparison methods, uses the shortest path pairwise distance matrix. Spectral methods are significantly faster than the fastest force-based methods, but they have a tendency to produce layouts with many overlapping nodes [7]. Civril et al, who recently independently rediscovered the algorithm, found that CMDS suffers less from this tendency than other popular spectral methods [2].…”
Section: Spectral Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Network layout can be calculated solely in dependence of network structure [26], only in dependence on node properties [6] or a combination of both network structure and network attributes [37,57]. The type of layout depends on the user task.…”
Section: Changing Mapping Of Attributesmentioning
confidence: 99%